Ausência de genotoxidade e redução dos efeitos genotóxicos induzidos por DOX da tintura de sementes de Helianthus annuus Linné (girassol) reveladas pelo ensaio do micronúcleo - Souza, Luiz Silva de (2012)
In addition to being an important source of nutrients, the potential therapeutic effectiveness of H. annuus L. seeds has been previously demonstrated; the beneficial properties of H. annuus L. seeds include an ability to relieve asthmatic symptoms, protective effects on the stomach, benefits to healing, and anti-inflammatory and anti-microbial properties. This research evaluated the mutagenicity and anti-mutagenicity of oil and tincture of H. annuus L. seeds using the micronucleus assay in bone marrow of mice. The interaction between these preparations and the genotoxic effects of doxorubicin (DOX) was also analyzed. Experimental groups were evaluated after 24-48 h of treatment with N-Nitroso-N-ethylurea (NEU) and DOX (positive controls), NaCl (a negative control), a sunflower tincture (250-2,000 mg.Kg-1 of THALS) and two sources of sunflower oils (250-2,000 mg.Kg-1 of POHALS and FOHALS). Anti-mutagenic assays were carried out using the sunflower tincture and oils separately and in combination with these controls. The frequency of micronucleated polychromatic erythrocytes (MNPCEs) was significantly different (p  0.05) between (i) the positive and negative control treatments, (ii) the positive controls and animals treated with THALS and (iii) animals treated with THALS and and THALS combined with the positive controls. However, a slight genotoxicity was observed in the animals treated with the combination of THALS+DOX. Both sources of oils (FOHALS and POHALS) revealed similar results; in these groups, the frequencies of MNPCEs were similar to those observed in negative controls. Statistically significant differences were also observed between the sunflower oil treatments and their associated positive controls. There was no genotoxicity (clastogenicity/aneugenicity) observed in THALS, POHALS and FOHALS regardless of the dose, time (except FOHALS) and gender of mouse (except POHALS and FOHALS). The moderate anti-genotoxic effects of THALS suggest a potential slight protective mechanism against DOX-induced genotoxic effects.